0632 Time of Day and Time on Task Effects on Working Memory and Sleepiness of Bus Drivers. (12th April 2019) - Maghsoudipour, Maryam; Moradi, Ramin; Pouyakian, Mostafa; Yaseri, Mehdi
Abstract: Introduction: Fatigue and sleepiness have direct effects on vigilance, and cognitive functions of drivers. The objective of this study was to analyze individual bus drivers' characteristics and work shift parameters and relation to the working memory performance and sleepiness. Methods: This prospective study was conducted on 35 inter-city bus drivers by convenience sampling. We collected data during the time span of a 24-hour round trip by using the demographic questionnaire, Epworth Sleepiness Scale (ESS), Karolinska Sleepiness Scale (KSS), and reversed digit span memory test (part of the Wechsler-Adult Intelligence Test). A linear mixed model was used for statistic analysis. Results: The mean (± SD) of Epworth Sleepiness Scale score was 6.4 (±2.7). 12.5% of drivers had excessive daytime sleepiness according to ESS results. The circadian effect of time of day on the drivers' working memories was statistically significant (P=0.001), and the working memory was minimum at 04:00 am (± 1). Additionally, the differences in sleepiness at different times of day were statistically significant (P=0.001); with the highest score at 04:00 am (± 1). Time on task and time of sleep parameters did not show a significant effect on working memory (p> 0.05). Time on task parameter affected sleepiness significantly (p=0.024). Conclusion: The circadian factor was the most important predictor of cognitive performance compared to time on task (fatigue) and time of sleep. Although, time on task had a significant effect on sleepiness and sleepiness significantly decreased working memory. We conclude that optimizing the drivers' schedule is the most important intervention to optimize drivers' performance and increase road safety. Support (If Any): Not